FORMATION OF THE ELECTION SYSTEM IN THE REPUBLIC OF UZBEKISTAN (1991-2000) (Scientific journal of the Fergana State University, 2023)
This article deals with the reforms carried out in the electoral sphere of the country after the declaration of state independence of the Republic of Uzbekistan and their implementation in practice, as well as the extensive use of national and international experience in the formation of the electoral system.